On “Officer Professional Military Education Policy” and its enlightenment - Liu Yue; Xiong Longfei; Liu Yunzheng (SHS Web of Conferences, 2023)
"Officer Professional Military Education Policy" is an important guide for M army. This paper aims to deeply explore the core content of its military education and its development trend, and draw useful experience from it, so as to promote the innovation of military education and provide reference for training new military talents with international competitiveness.